HUBUNGAN KOMPETENSI PROFESIONAL GURU KIMIA DAN MOTIVASI BELAJAR SISWA DENGAN PRESTASI BELAJAR KIMIA SISWA - Mujadalah Mujadalah; Urwatil Wutsqo Amry; Wirentake Wirentake (Fitrah, 2022)
Abstract: This study aims to find out how strong the correlations between : teachers' professional competence and student achievement in chemistry, (b) student motivation and student achievement, and (c) teachers' professional competence together with student motivation and student achievement. The population of this study is 3081 of Senior High Schools students (SMA) enrolled in 8 (eight) schools in Mataram. The Sampling in this study is multistage random sampling, acounting 263 studentsas the sample. The single correlation between the results of professional competence of teachers and student achievement, with t count ( 6234 ) > t table (1.651 ) at 5 % significance level. It means that the professional competence of chemitry teachers has a positive and significant relationship toward student achievement. The results of the second single correlation between student motivation and student achievement at the significant level of 5 % , with t count (3976 ) > t table ( 1.651 ). It mean that students' motivation has a positive and significant relationship toward student achievement. The results of multiple correlation between teachers' professional competence and students motivation toward student achievement, with F count ( 22 . 485 ) > F ( 3,031 ) at the 5 % significance level. It means that the professional competence of chemistry teachers and students motivation collectively have a positive relationship and significantly associated with student achievement.